2018
DOI: 10.1002/aenm.201802369
|View full text |Cite
|
Sign up to set email alerts
|

Nanowires in Energy Storage Devices: Structures, Synthesis, and Applications

Abstract: great significance in solving the current energy crisis and environmental problems in human society. [1] Solar energy, wind energy, hydropower, and nuclear power are used as environmentally friendly and sustainable energy sources. [2] However, the seasonal characteristic, regionalism, and discontinuity make it hard to use the clean energy directly in the industries and daily life. Therefore, how to store these energy sources is a hot spot of concern. Currently, different kinds of energy storage technologies fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
136
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 210 publications
(136 citation statements)
references
References 169 publications
0
136
0
Order By: Relevance
“…These materials have been utilized in the field of electrocatalysis and energy conversion. [65][66][67] As for electrocatalysts of the ORR, 1D MÀ NÀ C materials have also attracted great attention. [68] The morphologies of reported 1D MÀ NÀ C materials include nanofibers, nanowires, nanorods, and nanotubes.…”
Section: D Metal-nitrogen-carbon Materials For the Oxygen Reduction mentioning
confidence: 99%
“…These materials have been utilized in the field of electrocatalysis and energy conversion. [65][66][67] As for electrocatalysts of the ORR, 1D MÀ NÀ C materials have also attracted great attention. [68] The morphologies of reported 1D MÀ NÀ C materials include nanofibers, nanowires, nanorods, and nanotubes.…”
Section: D Metal-nitrogen-carbon Materials For the Oxygen Reduction mentioning
confidence: 99%
“…In this work, we use a one‐step hydrothermal process to grow large‐area, uniform and well‐aligned NVPF arrays on a flexible freestanding carbon nanofiber membrane. As compared to other carbon substrates, 1D carbon nanofiber architecture could form efficient current pathways, shorten the ion diffusion length and provide high surface area, increasing large electrolyte–electrode contact area . The growth process of NVPF can be controlled by changing the reaction time.…”
Section: Introductionmentioning
confidence: 99%
“…As compared to other carbon substrates, 1D carbon nanofiber architecture could form efficient current pathways, shorten the ion diffusion length and provide high surface area, increasing large electrolyte-electrode contact area. [45,46] The growth process of NVPF can be controlled by changing the reaction time. This electrode design has the unique merits during the Na + extraction/ insertion process.…”
Section: Introductionmentioning
confidence: 99%
“…A series of different ternary metal oxide electrode materials were produced such as Ni-Co-Fe, Ni-Co-Al, and Ni-Co-Cu. [31] It has been reported that the presence of an appropriate amount of oxygen vacancies can greatly increase the specific capacitance of NiO and ZnO, [32,33] which may result from the increase of ion conduction velocity caused by surface defects. Then, morphology has a great influence on electrochemical properties of the material.…”
Section: Introductionmentioning
confidence: 99%